(untitled) (Pubmet, 2025)
Journal articles and books are generally considered the traditional published outputs that result at the end of the scholarly process and constitute the scholarly record. With rapid advancements in scholarly communication, the type and complexity of published outputs have increased significantly in recent times to include works such as datasets, software, conference presentations, as well as the elements that go into the creation of these outputs (e.g., peer reviews and preprints) (Lavoie et al, 2014). As such, the definition of the scholarly record has expanded to include published outputs, the inputs, the relationships between them, as well as the context around each output that can be inferred from the associated metadata. Preserving the integrity of such a comprehensive and constantly evolving scholarly record is a key component of the overall efforts to preserve research integrity. Open scholarly infrastructure plays an important role in this undertaking by providing trust signals that enable the assessment of the trustworthiness of published outputs. Crossref is a not-for-profit membership organisation that provides open scholarly infrastructure to enable the scholarly community to provide and deposit metadata about the content that they produce. This open and rich metadata provides a framework for detecting trustworthiness, thereby helping to preserve the integrity of the scholarly record.